Manipulating room-temperature phosphorescence via lone-pair electrons and empty-orbital arrangements and hydrogen bond adjustment. Issue 22 (30th May 2022) - Sun, Haodong; Xie, Zongliang; Wang, Hailan; Wu, Yazhang; Du, Beibei; Guan, Cao; Yu, Tao
Abstract : Switchable and tunable RTP properties: by rational arrangement of lone-pair electrons and empty p-orbitals in molecular design, and by adjustment of hydrogen bonds in crystal packing, switchable and tunable RTP of BP derivatives is achieved. Abstract : Most pure organic materials with room-temperature phosphorescence (RTP) possess heteroatoms with lone-pair electrons or boron atoms with empty p-orbitals leading to an accelerated k isc . In this work, we present a strategy to efficiently tune the RTP emission through lone-pair electrons and empty orbital arrangements, and rotation of the borate pinacol (Bpin) group. In BP2Bpin, the empty p-orbitals are occupied by neighboring lone-pair electrons, and no RTP emission is observed. Meanwhile, strong RTP emission is detected in BP4Bpin due to the separation of the lone-pair electrons and empty p-orbitals. Furthermore, the crystalline n -BP4Bpin possesses green PL and longer RTP emission at ca. 490 and 525 nm ( τ = 61 ms) and c -BP4Bpin shows white PL and short RTP emission at ca. 520 nm ( τ = 15 ms). The emission of crystalline n -BP4Bpin changes from green-yellow to blue-white light with the temperature increasing from 25 °C to 60 °C. Detailed single-crystal and computational analyses are preformed to illustrate the diverse PL and RTP properties. This work enables the manipulation of RTP emission by adjusting the arrangements of lone-pair electrons and empty orbitals and the change of emission through controlling the ISC processes. It provides a strategy for tuning the PL and RTP properties of organic light-emitting materials.